Pre-operative Screening of Patients for Hepatitis B and C virus - Hamid Mahmood, Kashif Jahangir, Hizb-ur-Rahman (Pakistan Journal of Ophthalmology, 2012)
Purpose: To screen hepatitis B and C among patients and to establish policies to avoid hepatitis spread in an almost fully preventable setting. Material and Methods: This was a Prospective observational study. A total of 543 patients admitted in eye ward were screened for hepatitis B and C, by Immunochromatographic (ICT) method. The study was conducted from August 2010 to October 2011. Results: Out of the total of 543 patients admitted in eye ward 255 of them were male and 288 were female. A total of 145 (27%) patients were found to be hepatitis C (HCV) positive and 11 (2.02%) were hepatitis B virus (Hbs) positive. Conclusion: Such a high percentage of hepatitis C positive patients is alarming not only for patients but for health workers dealing with such patients. Proper sterilization protocols should be implemented, and followed that would help in prevention of spread of the disease.